(untitled) (Research, Society and Development, 2020)
Objective: To develop educational activities on health and law with pregnant women attended at a child-friendly hospital (HAC) in the city of Teresina-PI. Methodology: This is a descriptive study, aimed at pregnant women attended at Dona Evangelina Rosa Maternity. The actions took place through the distribution of educational materials and lectures with exchange of experiences and knowledge about breastfeeding and rights guaranteed to pregnant women. Results: In total, 30 pregnant women attended at the maternity hospital attended the lectures and had access to educational materials. There were 8 meetings, in each one of them a group led by a multiprofessional team, addressing the rights of childbirth at the time of the companion, the skin-to-skin contact with the baby after delivery, as well as the factors that can make it difficult to correct breastfeeding and exclusive breastfeeding, seeking to identify them and provide ways to avoid them. Conclusion: Through the actions developed it was noticeable that the lectures and the distribution of informative materials were important in the dissemination of knowledge to the pregnant women, however, there was no participation of a larger number of pregnant women in these educational actions, since it was not mandatory. Therefore, it is fundamental that these lectures become fundamental pieces in the prenatal care of pregnant women in maternity wards.